Tackling multiple discrimination : practices, policies and laws - European Commission. Directorate-General for Employment , Social Affairs and Equal Opportunities (Office for Official Publications of the European Communities, 2007)
Summary (s. 5-7).
Keywords: yhdenvertaisuus : EU-maat; vähemmistöt : EU-maat; työmarkkinat : EU-maat